# 8x(x-9)+(7-x)8x=64

## Simple and best practice solution for 8x(x-9)+(7-x)8x=64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 8x(x-9)+(7-x)8x=64 equation:

Simplifying
8x(x + -9) + (7 + -1x) * 8x = 64
Reorder the terms:
8x(-9 + x) + (7 + -1x) * 8x = 64
(-9 * 8x + x * 8x) + (7 + -1x) * 8x = 64
(-72x + 8x2) + (7 + -1x) * 8x = 64
Reorder the terms for easier multiplication:
-72x + 8x2 + 8x(7 + -1x) = 64
-72x + 8x2 + (7 * 8x + -1x * 8x) = 64
-72x + 8x2 + (56x + -8x2) = 64
Reorder the terms:
-72x + 56x + 8x2 + -8x2 = 64
Combine like terms: -72x + 56x = -16x
-16x + 8x2 + -8x2 = 64
Combine like terms: 8x2 + -8x2 = 0
-16x + 0 = 64
-16x = 64
Solving
-16x = 64
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Divide each side by '-16'.
x = -4
Simplifying
x = -4